AKUNTABILITAS DESA MEMBANGUN IMPLEMENTASI KEWENANGAN LOKAL DALAM PELAKSANAAN KAMPUNG MEMBANGUN MENUJU KAMPUNG MANDIRI PADA KAMPUNG MURIS KECIL, KABUPATEN JAYAPURA, PAPUA - Sato, Raymond; Laksmono, Bambang Shergi (Jurnal Pembangunan Manusia, 2020)
Village development is a new concept of development paradigm from the Government driven development model or community driven development into Village driven development which positions the village as the subject of development. Villages that drive development with local initiatives are also the spirit of the government's ideals as well as the third point of the President's Nawacita which states that it will develop Indonesia from the periphery by Strengthening Regions and Villages within the framework of a unitary state. The local authority of the Muris Kecil village recognized by the central, provincial and district governments is evident in the provision of large funds, but in the 2015 Village Development Index, the village of Muris Kecil is classified as a village with a lagging village category. Because it is interesting to see how the implementation of development management in the village of Muris Kecil to independent villages, where transparency and accountability in planning, implementation, and reporting of each development activity is carried out. This research was conducted using a qualitative approach and using in-depth interviewing techniques and observation. The results of the research have shown that the implementation of local authority is hampered by a lack of Human Resources and community access to information regarding the importance of development to improve people's welfare, the weak role of local institutions in supporting community participation in development activities, and the lack of awareness of village officials to realize governance accountability-based village governance.